CORRELACIÓN DEL PERFIL DE TEXTURA (TPA) ENTRE EL ANÁLISIS INSTRUMENTAL Y EL ANÁLISIS SENSORIAL DEL QUESO FRESCO - Unach (2019)
The sensory texture can determine the level of acceptance of food, and therefore it becomes a quality parameter. Quantifying this property is difficult since the flow behavior in the mouth is very complex. Therefore, texture profile analysis (TPA) has become an instrumental procedure that simulates chewing, however, there is no defined protocol regarding the variables that can affect the TPA at the time of testing. In this research, the sensory texture analysis of fresh cheese was compared and contrast with instrumental texture parameters through the application of different protocols. The sensory analysis was performed with a panel of 17 semi-trained judges. For the instrumental analysis, cylindrical samples of 2 and 3cm diameter and cubic samples of 1.5 and 2cm³ were used, at two percentages of compression (50 and 75%) and three speed levels (0.3 mm/s, 0.7 mm/s or 1mm/s). In this study it was found that the shape and size as the compression percentage of the test used in the equipment are factors that affect the results of the instrumental texture parameters. As the most relevant conclusions, it is suggested to use the protocol that uses cylindrical samples of 3cm diameter and 2cm3 cubic samples, both compressed to 75% since this percentage of compression offers more information at the time of the test and better groups the sensory analysis data and instrumental and multivariate methods are used.